Oral prednisolone suppresses skin inflammation in a healthy volunteer imiquimod challenge model - Assil, Salma; Buters, Thomas P.; Hameeteman, Pieter W.; Hallard, Charlie; Treijtel, Nicoline; Niemeyer – Van der Kolk, Tessa; de Kam, Marieke L.; Florencia, Edwin F. I. I. I.; Prens, Errol P.; van Doorn, Martijn B. A.; Rissmann, Robert; Klarenbeek, Naomi B.; et al. (Frontiers in Immunology, 2023)
Imiquimod (IMQ) is a registered topical agent that induces local inflammation via the Toll-like receptor 7 pathway. Recently, an IMQ-driven skin inflammation model was developed in healthy volunteers for application in proof- of- pharmacology trials. The aim of this study was to profile the cellular, biochemical and clinical effects of the marketed anti-inflammatory compound prednisolone on the IMQ model. A randomized, double-blind, placebo-controlled study was conducted in 24 healthy volunteers. Oral prednisolone (0.25 mg/kg/dose) or placebo (1:1) was administered twice daily for 6 consecutive days. Two days after treatment initiation with prednisolone or placebo, 5mg imiquimod (IMQ) once daily for two following days was applied under occlusion on tape stripped skin of the back for 48 hours in healthy volunteers. Non-invasive (imaging and biophysical) and invasive assessments – skin punch biopsies and blister induction – were performed as well as IMQ ex vivo stimulation on whole blood. Prednisolone reduced blood perfusion and skin erythema following 48h of IMQ application (95% CI [-26.4%, -4.3%], p=0.0111 and 95% CI [-7.96, -2.13], p=0.0016). Oral prednisolone suppressed the IMQ-elevated total cell count (95% CI [-79.7%, -16.3%], p=0.0165), NK and dendritic cells (95% CI [-68.7%, -5.2%], p=0.0333, 95% CI [-76.9%, -13.9%], p=0.0184) and classical monocytes (95% CI [-76.7%, -26.6%], p=0.0043) in blister fluid. Of note, TNF, IL-6, IL-8 and Mx-A responses in blister exudate were also reduced by prednisolone compared to placebo. Oral prednisolone suppresses IMQ-induced skin inflammation, which underlines the value of this cutaneous challenge model in clinical pharmacology studies with novel anti-inflammatory compounds. In such studies, prednisolone can be used as benchmark.